Poverty reduction in a refugee-hosting economy: A natural experiment - Maystadt, Jean-François (International Food Policy Research Institute, 2011)
The role of migration in reducing poverty in developing countries has been investigated mainly from the perspective of migrants and their relatives. This paper exploits the time and spatial variations in the way households in the region of Kagera (Tanzania) traced between 1991 and 2004 have been affected by massive refugee inflows to assess how migration may affect poverty in the hosting communities. Large population inflows from Burundi and Rwanda have improved the welfare of the hosting population, particularly for the poor. Despite the process of structural transformation observed in the refugee-hosting economy, such pro-poor development is mainly explained by improved agricultural labor productivity and income diversification among the poor.